2019
DOI: 10.1002/ctpp.201900041
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion properties of electron acoustic waves in degenerate and non‐degenerate quantum plasmas

Abstract: The longitudinal response functions are used to generalize the dispersion properties of electron acoustic waves (EAWs) in the presence of quantum recoil, for isotropic, non-relativistic, degenerate/non-degenerate plasmas. In order to study the EAWs, the constituents of non-degenerate (thermal) plasma are considered to be of two groups of electrons having different number density and temperature, namely the cold electrons and the hot electrons. Similarly in degenerate (Fermi) plasma the two population of electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Within the basic parameter permissible range, it is noticed that for a certain value of the parameter set the nonlinear coefficient of an Equation (17), that is, A tends to zero. This means the nonlinear part of the derived very well-known KdV equation is going to be annihilated and, this breaks the solitary waves form.…”
Section: Modified Korteweg De-vries Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the basic parameter permissible range, it is noticed that for a certain value of the parameter set the nonlinear coefficient of an Equation (17), that is, A tends to zero. This means the nonlinear part of the derived very well-known KdV equation is going to be annihilated and, this breaks the solitary waves form.…”
Section: Modified Korteweg De-vries Equationmentioning
confidence: 99%
“…Nonlinear features in theoretical physics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] associated with fluid mechanics, solid-state physics, plasma physics, optical fibres, biophysics, chemical kinematics, chemical physics, and geochemistry are revealed through framing mathematical models, derive nonlinear evolution equations (NLEEs), and getting its solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Q-machine, inserting a grid Barkan et al, [14] Nakamura et al, [15] and Melrino et al [16] observed the plasma column in laboratory experiments. Some recent novel and important investigations have been reported in dusty plasma, [17,18] ordinary plasmas, [19][20][21][22] and quantum plasmas [23][24][25] where DASWs and IASWs structures have been extensively studied in the framework of two-dimensional nonlinear Kadomtsev-Petviashvili (KP), Kadomtsev-Petviashvili-Burgers (KPB) equations, three dimensional Zakharov-Kuznetsov (ZK), and Zakharov-Kuznetsov-Burgers (ZKB) equations. These investigations [17][18][19][20][21][22][23][24][25] might be very much effective to derive another nonlinear evolution equations from complicated physical problems modelled by complex nonlinear partial differential equations arising in mathematical physics, hydrodynamics, fluid mechanics, mathematical biology, plasma physics, engineering disciplines, chemistry, and many other natural sciences through straightforward calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Fahad et al studied the dispersion features of EA waves in non-relativistic quantum recoil with isotropic non-degenerate system. The coefficients of absorption for Landau damping were discussed for laser-produced plasmas [22]. Also, Yahia et al investigated the head-on EA collisions in quasi-elastic case in magnetized nonthermal plasma.…”
Section: Introductionmentioning
confidence: 99%